PUSAT KREATIVITAS ANAK DI PONTIANAK - Adilla Chairiah; Lestari Lestari; Irwin Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Children are the future successors of the nation who must be equipped with supporting knowledge and education. One of the factors that influence the development of children are children’s creativity. Creativity is important for children because creativity is useful as a human need to be creative, creativity allows children to express themselves and thoughts in solving problem and many more. Creativity activities in schools are limited, namely 4-5 hours due to strict curriculum (Kemendikbud, 2012). The facilities that support the development of children's creativity in Pontianak is quite limited. This condition shows that Pontianak needs facilities that support the development of children's creativity, namely the Child Creativity Center in Pontianak. The design method starts from identifying the problem by looking at the issues, data collecting consists of primary data and secondary data, and then the data is analyzed which produced pre design drawing. The emphasis on the design is child-friendly which includes aspects of safety, comfort, freedom and stimulates children's potential. This concept produces a mass building design with a circular shape that has been transformed. The use of the right colors, shapes, materials and dimensions is the core of the design of the Children's Creativity Center in Pontianak.